IMPLEMENTASI KEGIATAN MUSYAWARAH KUBRO KITAB FATHUL QARIB DALAM MELATIH PUBLIC SPEAKING SANTRI PONDOK PESANTEN HUDAYA SUKOPURO JOMBANG - Irsyad Sibro Malisi; Shobihus Surur (STAI Nurul Falah Airmolek, 2025)
Musyawarah Kubro Fathul Qarib is an in-depth learning activity of the book of Fathul Qarib which is oriented towards deepening the knowledge of fiqh in the Pondok Pesantren environment. This activity not only requires students to actively argue based on arguments or other fiqh book references, but also becomes an effective medium in practicing public speaking skills. This study aims to determine the implementation of Kubro deliberation activities at Hudaya Sukopuro Islamic Boarding School, and describe its role in training students' public speaking. The research used descriptive qualitative methods with data collection techniques in the form of interviews, observation, and documentation. The results showed that Musyawarah Kubro plays an important role in deepening the understanding of fiqh and developing students' speaking skills, as well as being a forum for scientific discussions across educational levels under the guidance of kiai and ustadz. This activity is effective in practicing public speaking through positive coercion, so it is expected to be able to produce preachers and communicators who are ready to plunge into society.